FUNCTIONAL FECAL INCONTINENCE IN CHILDREN (DIFFERENTIAL DIAGNOSTICS AND TREATMENT APPROACHES) - V.N. Kopeikin; E.N. Fedulova; O.A. Tutina; O.V. Fedorova; I.I. Tsalolikhina (Педиатрическая фармакология)
Impairment of the intestinal content continence, a common clinical situation with various pathogenetic mechanisms. Disease proceeds with the child’s maladjustment events. 33 cases of encopresis have been analyzed. This condition has various clinical and instrumental diagnostic criteria depending on the origin which simplifies differential diagnostics. Using a differential diagnostics table helps expedite the process of making a diagnosis and hence start an adequate treatment in a timely manner.Key words: encopresis, differential diagnostics, treatment, children.